The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1126/science.aac9786
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic activation of a DNA damage response causes cell-to-cell mutation rate variation

Abstract: Cells rely on the precise action of proteins that detect and repair DNA damage. However, gene expression noise causes fluctuations in protein abundances that may compromise repair. For the Ada protein in Escherichia coli, which induces its own expression upon repairing DNA alkylation damage, we found that undamaged cells on average produce one Ada molecule per generation. Because production is stochastic, many cells have no Ada molecules and cannot induce the damage response until the first expression event oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
214
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(227 citation statements)
references
References 37 publications
13
214
0
Order By: Relevance
“…Regardless of the underlying mechanism we have found that the slowing down of diffusion allows for visualization and even accurate counting of fluorescent proteins at exceptionally low abundances, using conventional TIRF microscopy setups 10,11 . As opposed to chemical fixation protocols, this mechanical fixation can be achieved with no loss of fluorescence, and extensive controls with photobleaching steps and tandem dimer FPs 11 suggest that we do detect close to all mature fluorescent molecules.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Regardless of the underlying mechanism we have found that the slowing down of diffusion allows for visualization and even accurate counting of fluorescent proteins at exceptionally low abundances, using conventional TIRF microscopy setups 10,11 . As opposed to chemical fixation protocols, this mechanical fixation can be achieved with no loss of fluorescence, and extensive controls with photobleaching steps and tandem dimer FPs 11 suggest that we do detect close to all mature fluorescent molecules.…”
Section: Introductionmentioning
confidence: 90%
“…For instance, in bacteria, a large fraction of the proteome is present in just a handful copies per cell 8 . These proteins have been very difficult to analyze 9 , and include many key regulatory proteins that contribute greatly to the phenotypic heterogeneity of cells 10 . We recently developed a microfluidic platform, termed MACS for M icrofluidics- A ssisted C ell S creening, to address the limitations of flow cytometry and traditional microscopy 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of this focus, we have included materials based on the work of Vilar et al . (2003) and, more recently, Uphoff et al . (2016) on the roles of regulatory noise, including the stochastic processes that underlie DNA–protein interactions (Elowitz et al ., 2002; Maheshri and O’Shea, 2007).…”
Section: Process Description and Outcomesmentioning
confidence: 95%